Palladium (II) Complex Enhances ROS-Dependent Apoptotic Effects via Autophagy Inhibition and Disruption of Multiple Signaling Pathways in Colorectal Cancer Cells - Aydinlik, Seyma; Erkisa, Merve; Ari, Ferda; Celikler, Serap; Ulukaya, Engin (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Inhibition of autophagy is reported to be a therapeutically effective strategy in overcoming resistance that is a deadly outcome in cancer. One of the most common reasons for chemo-resistance to treatment is the patients with tumors exhibiting a KRAS mutation, which occurs in approximately 40% of colorectal cancer patients. Objective: Hence, we assessed whether a Palladium (Pd)(II) complex is a promising anticancer complex, compared to 5-fluorouracil in KRAS wt HT-29 and KRAS mutant HCT-15 cells. Methods: HCT-15 and HT-29 cells were used for colorectal cancer and Chloroquine (CQ) was used as an inhibitor of autophagy. In this context, cells were treated with Pd(II) complex and 5-FU in combination with CQ for 48h and cell viability was measured by SRB assay. Cell death mode was examined with M30 and M65 ELISA assays, using annexin V/propidium iodide. Autophagy was determined by Acridine Orange (AO) staining. Furthermore, the expressions of various autophagy and apoptosis-related proteins were evaluated with Western blotting. Luminex assay and the level of Reactive Oxygen Species (ROS) were examined. Results: Cell viability was found to decrease in a dose-dependent manner and CQ enhanced cytotoxic effect in Pd(II) and 5-FU treated cells in colorectal cancer cells. Our data showed that inhibition of autophagic flux significantly increased intrinsic apoptosis through the activation of ROS. We showed that combinatorial treatment with CQ induced apoptosis via the caspase-dependent mitochondrial pathway. Luminex analysis revealed that the combination resulted in a down-regulation of NF-ΚB/AKT/CREB signaling pathways in both cell lines, however, decreased Erk1/2 protein expression was only observed after treatment with CQ combination in HCT-15 cells. Conclusion: We suggest that the inhibition of autophagy along with Pd(II) and 5-FU treatment has a synergistic effect on KRAS-mutant colorectal cancer cells. Autophagy inhibition by CQ promotes apoptosis via blockade of the NF-ΚB/AKT/CREB and activation of ROS.
Keywords: autophagy